PENGARUH KOMPETENSI DAN DISIPLIN TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SEPUTIH AGUNG KABUPATEN LAMPUNG TENGAH - Rudi Setiaji; Suharto Suharto; Afdal Mazni (Universitas Muhammadiyah Metro, 2021)
This study aims to determine and test empirically: The Effect of Competence on Employee Performance at the Seputih Agung District Office, Central Lampung Regency. The Effect of Discipline on Employee Performance at the Seputih Agung District Office, Central Lampung Regency. The Effect of Competence and Discipline on Employee Performance at the Seputih Agung District Office, Central Lampung Regency. Respondents in this study were 37 employees of the Seputih Agung District Office, Central Lampung Regency. The results of the study prove that competence has an effect on employee performance at the Seputih Agung subdistrict office, Central Lampung regency. Discipline affects employee performance at the Seputih Agung subdistrict office, Central Lampung regency. Competence and Discipline affect Employee Performance at the Seputih Agung District Office, Central Lampung Regency. The magnitude of the influence of competence and discipline on employee performance at the Seputih Agung sub-district office in Central Lampung regency is 64.6%, while the remaining 35.4%% is influenced by other factors outside the model included in this study